2003
DOI: 10.1038/nature02166
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterization of the human centrosome by protein correlation profiling

Abstract: The centrosome is the major microtubule-organizing centre of animal cells and through its influence on the cytoskeleton is involved in cell shape, polarity and motility. It also has a crucial function in cell division because it determines the poles of the mitotic spindle that segregates duplicated chromosomes between dividing cells. Despite the importance of this organelle to cell biology and more than 100 years of study, many aspects of its function remain enigmatic and its structure and composition are stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
1,114
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,221 publications
(1,168 citation statements)
references
References 30 publications
48
1,114
2
4
Order By: Relevance
“…Analysis of the subcellular localization of endogenous S5A protein revealed that, similar to ID1, a fraction of cellular S5A is localized at centrosomes. Similar centrosomal localization patterns have been reported for other components of the proteasome (Freed et al, 1999;Wigley et al, 1999;Fabunmi et al, 2000;Andersen et al, 2003), Localization of proteasome components at the centrosome might be crucial for centrosome duplication (reviewed in Hinchcliffe and Sluder, 2001). Supporting an important function of proteasome components during centrosome duplication are our findings that knockdown of S5A by shRNA caused an increase of cells with supernumerary centrioles (Figure 4).…”
Section: Discussionsupporting
confidence: 88%
“…Analysis of the subcellular localization of endogenous S5A protein revealed that, similar to ID1, a fraction of cellular S5A is localized at centrosomes. Similar centrosomal localization patterns have been reported for other components of the proteasome (Freed et al, 1999;Wigley et al, 1999;Fabunmi et al, 2000;Andersen et al, 2003), Localization of proteasome components at the centrosome might be crucial for centrosome duplication (reviewed in Hinchcliffe and Sluder, 2001). Supporting an important function of proteasome components during centrosome duplication are our findings that knockdown of S5A by shRNA caused an increase of cells with supernumerary centrioles (Figure 4).…”
Section: Discussionsupporting
confidence: 88%
“…To date, partial centrosome localization has been shown for several proteins involved in ubiquitination and proteasomal degradation (Fabunmi et al, 2000;Andersen et al, 2003). We now show that a fraction of antizyme 1 associates with maternal centrioles and modulates daughter centriole amplification.…”
Section: Discussionmentioning
confidence: 62%
“…Recent evidence has shown that many components of the proteasomal degradation machinery concentrate at centrosomes and form active proteasomal complexes (Fabunmi et al, 2000;Andersen et al, 2003). We show here that antizyme 1, a mediator of ubiquitin-independent proteasomal degradation and its inhibitor, AZI, localize to centrosomes and are functionally important centrosome-associated proteins.…”
Section: Introductionmentioning
confidence: 50%
“…Andersen et al originally identified CEP63 in a proteomic analysis of the human centrosome and confirmed centrosomal localisation by expressing GFP construct in cells (Andersen et al, 2003). At the time we isolated XCEP63, no CEP63 characterization studies had been published and consequently no function had been ascribed.…”
Section: Xcep63 As An Atm and Atr Target Of Interestmentioning
confidence: 95%